Early viral suppression improves neurocognitive outcomes in HIV-infected children. (28th January 2015) - Crowell, Claudia S.; Huo, Yanling; Tassiopoulos, Katherine; Malee, Kathleen M.; Yogev, Ram; Hazra, Rohan; Rutstein, Richard M.; Nichols, Sharon L.; Smith, Renee A.; Williams, Paige L.; Oleske, James; Muller, William J.
<x xml:space="preserve">Abstract</x> Objective: To estimate the association of age of viral suppression and central nervous system penetration effectiveness (CPE) score with neurocognitive functioning among school-age children with perinatally acquired HIV infection (PHIV+). Design: We analyzed data from two US-based multisite prospective cohort studies. Methods: Multivariable general linear regression models were used to evaluate associations of age at viral suppression and CPE scores (of initial antiretroviral therapy regimen and weighted average) with the Wechsler Intelligence Scale for Children, Third or Fourth Edition neurocognitive assessments [Full-Scale Intelligence Quotient (FSIQ); Performance IQ/Perceptual Reasoning Index (PIQ/PRI); and Verbal IQ/Verbal Comprehension Index (VIQ/VCI)], adjusted for demographic and clinical covariates. Sensitivity analyses were stratified by birth cohort (before versus after 1996). Results: A total of 396 PHIV+ children were included. Estimated differences in mean FSIQ (comparing virally suppressed versus unsuppressed children) by each age cutoff were 3.7, 2.2, 3.2, 4.4, and 3.9 points at ages 1, 2, 3, 4, and 5, respectively. For PIQ/PRI, estimated mean differences were 3.7, 2.4, 2.2, 4.6, and 4.5 at ages 1 through 5, respectively. In both cases, these differences were significant only at the age 4 and 5 thresholds. After stratifying by birth cohort, the association between age at suppression and cognitive function persisted only among those born after 1996. Age at viral suppression was not associated with VIQ/VCI; CPE score was not associated with FSIQ, verbal comprehension, or perceptual reasoning indices. Conclusion: Virologic suppression during infancy or early childhood is associated with improved neurocognitive outcomes in school-aged PHIV+ children. In contrast, CPE scores showed no association with neurocognitive outcomes.